The Way of the Barbarians : Redrawing Ethnic Boundaries in Tang and Song China - Yang, Shao-yun (Book collections on Project MUSE., 2019)
"The Way of the Barbarians examines a critical period in the development of conceptions of Chinese identity and of foreignness. After tracing thought about culture, customs, ritual, and ethnicity to BCE classical texts, Shao-yun Yang focuses on the meaning and boundaries of Chineseness during the Tang (618-907 CE) and Song (960-1276 CE) dynasties. This period is widely seen as a watershed during which Chinese society was transformed in fundamental ways by population growth, commercialization, urbanization, technological advances, the decline of the long-dominant 'great clan' elite, and the rise of a new literati elite via the greatly expanded civil service examination system. Accompanying shifts occurred in how the Chinese defined themselves as a people and understood their relationship to the rest of the world. Previous scholarship has postulated a ninth-century shift from a spirit of cosmopolitanism--which identified foreign peoples as 'barbarians' who were morally and culturally inferior but who could become Chinese through a 'civilizing' process of acculturation--to one of ostracism. Another view identifies a twelfth-century shift from a traditional notion of culturalism to a new Chinese nationalism, which considered foreigners to be immutably and dangerously 'other' and called for their exclusion from the Chinese world, by force if necessary. This carefully argued intellectual history challenges previous thinking regarding the balance between culture, nation, and race in premodern Chinese identity and engages with ongoing debates over the applicability and relevance of the concept of ethnicity to premodern China"--